Genomic Evolution of White Spot Syndrome Virus in Shrimp: Insights from Transposon Dynamics - Zhouquan Li; Guanghua Huang; Jingyi Zhang; Mingyou Li; Zhizhi Liu; Sihua Peng; Rui Wang; Dong Liu (Biology, 2025)
White spot syndrome virus (WSSV) has emerged as a significant threat to global shrimp aquaculture, causing economic losses because of its rapid spread and high mortality rates. This study aims to elucidate the genetic and evolutionary dynamics of WSSV through a comprehensive genome analysis. Utilizing 27 complete genome sequences sourced from public databases, this study investigates the genetic variability, potential recombination events, and evolutionary patterns of WSSV. Our results identified multiple genomic deletions, 14 novel single-nucleotide polymorphism sites, and variable number tandem repeats across different strains, underscoring the virus’s genetic diversity. A recombination event between freshwater and marine strains highlights a complex transmission pathway, potentially facilitated by aquaculture practices. A phylogenetic tree constructed using ancestral genes suggests that WSSV originated in Southeast Asia and subsequently globally spread, influenced by both natural and anthropogenic factors. Genomic shrinkage of the virus occurred in time series, while the host’s viral infection induced transposon transposition and insertion into the earlier virus genome to provide a basis for genomic shrinkage. Our research emphasizes the importance of advanced molecular characterization and evolutionary models of the virus in understanding the spread of viral pathogens in aquaculture environments.